Corporate Legitimacy and COVID 19 Perceptions during the crisis in New York - Blanco-González, Alicia (2020)
The health emergency caused by COVID 19 has created a complex context from the health point of view, but also from a social, economic and political perspective, which has led to an uncertain situation regarding the future Before COVID 19 companies were focused on the United Nations Sustainable Development Goals During this situation we have seen how some of these goals improve ( while others worsen in societies where many of them were already surpassed It is disturbing to see the increase in the economic, salary and gender gap, the entrepreneurship problems, the loss of rights and liberties as well as the lack of respect to the elderly This situation made us think whether the institutions and companies were being responsible given the circumstances or not, if they were behaving in an ethical manner, and if their behavior during confinement was going to generate changes in the citizens' habits Therefore, we asked ourselves, are companies doing what they should? Are they legitimate? Are they adapting to this reality and helping the population? In this study, we present the responses to the questions regarding the relationship between companies and Covid 19 responsible behavior, impact on our future consumption habits, our government and the legitimacy of companies during the confinement in the United States